ARCHAEOLOGICAL INVESTIGATIONS IN PACARÁN, MIDDLE VALLEY OF RÍO CAÑETE: CURACAJO DE RUNAGUANAC - van Dalen Luna, Pieter (2014)
The results of archaeological research conducted in the locality of Pacarán, half the Cañete River Valley are presented. As a result of these investigations was identified sites corresponding to two periods of occupation: Late Intermediate represented by a socio-political entity known as Runaguanac and Tawantinsuyu.